K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

AH
Akai Haruma
Giáo viên
18 tháng 11 2021

Lời giải:

$(3x^5-2x^3+4x^2):2x^2=[2x^2(\frac{3}{2}x^3-x+2)]:2x^2$

$=\frac{3}{2}x^3-x+2$

15 tháng 10 2018

\(1.x^3+2x+x^2=x\left(x^2+x+2\right)\)

\(2.2x^3+4x^2+2x=2x\left(x^2+2x+1\right)=2x\left(x+1\right)^2\)

\(3.-3x^3-5x^2+8x=-3x^3+3x^2-8x^2+8x\)

\(=-3x^2\left(x-1\right)-8x\left(x-1\right)=\left(3x^2+8x\right)\left(1-x\right)\)

\(=x\left(3x+8\right)\left(1-x\right)\)

\(4.x^2+4x-5=x^2-x+5x-5=\left(x-1\right)\left(x+5\right)\)

\(5.6x^2-3x-3=6x^2-6x+3x-3=3\left(x-1\right)\left(2x+1\right)\)

\(6.3x^2-2x-5=3x^2+3x-5x-5=\left(x+1\right)\left(3x-5\right)\)

\(8.x^2-2x-4y^2-4y=\left(x-2y\right)\left(x+2y\right)-2\left(x+2y\right)\)\(=\left(x+2y\right)\left(x-y-2\right)\)

\(9.x^3+2x^2y+xy^2-9x=x\left(x^2+2xy+y^2-9\right)\)

\(=x\left(x+y-3\right)\left(x+y+3\right)\)

\(10.x^2-y^2+6x+9=\left(x+3-y\right)\left(x+3+y\right)\)

15 tháng 10 2018

Cam on ban nhieu nhe

3 tháng 11 2019

a) \(\left(6x^3+3x^2+4x+2\right):\left(3x^2+2\right)\)

\(=\left[3x^2\left(2x+1\right)+2\left(2x+1\right)\right]⋮\left(3x^2+2\right)\)

\(=\left[\left(3x^2+2\right)\left(2x+1\right)\right]⋮\left(3x^2+2\right)\)

\(=2x+1\)

b) \(\left(2x^3-22x^2-5x^2+60x+55x-150\right):\left(x-5\right)\)

\(=\left[\left(2x^3-22x^2+60x\right)-\left(5x^2-55x+150\right)\right]:\left(x-5\right)\)

\(=\left[2x\left(x^2-11x+30\right)-5\left(x^2-11x+30\right)\right]:\left(x-5\right)\)

\(=\left[\left(2x-5\right)\left(x^2-11x+30\right)\right]:\left(x-5\right)\)

\(=\left[\left(2x-5\right)\left(x^2-5x-6x+30\right)\right]:\left(x-5\right)\)

\(=\left[\left(2x-5\right)\left(x-5\right)\left(x-6\right)\right]:\left(x-5\right)\)

\(=\left(2x-5\right)\left(x-6\right)\)

\(=2x^2-17x+30\)

3 tháng 11 2019

d) \(\left(x^5+4x^3+3x^2-5x+15\right):\left(x^3-x+3\right)\)

\(=\left(x^5+5x^3+3x^2-x^3-5x+15\right):\left(x^3-x+3\right)\)

\(=\left[\left(x^5-x^3+3x^2\right)+\left(5x^3-5x^2+15\right)\right]:\left(x^3-x+3\right)\)

\(=\left[x^2\left(x^3-x+3\right)+5\left(x^3-x^2+3\right)\right]:\left(x^3-x+3\right)\)

\(=\left[\left(x^2+5\right)\left(x^3-x+3\right)\right]:\left(x^3-x+3\right)\)

\(=x^2+5\)

11 tháng 7 2021

\(\left(x^2+3\right)\left(3-x^2\right)\)

\(\left(x^2+3\right)\left(-x^2+3\right)\)

\(\left(-x^2+3\right).x^2+3\left(-x^2+3\right)\)

\(-x^2.x^2+3x^2+3\left(-x^2+3\right)\)

\(-x^2.x^2+3x^2-3x^2+9\)

\(-x^2.x^2+9\)

11 tháng 7 2021

\(\left(2x+5\right)\left(2x-5\right)\)

\(2x\left(2x-5\right)+5\left(2x-5\right)\)

\(4x^2-10x+5\left(2x-5\right)\)

\(4x^2-10x+10x-25\)

\(4x^2-25\)

25 tháng 7 2018

\(a.\left(2x-3\right)\left(4x^2+6x+9\right)-\left(2x+3\right)\left(4x^2-6x+9\right)\\ =\left(2x\right)^3-3^3-\left[\left(2x\right)^3+3^3\right]\\ =8x^3-9-\left(8x^3+9\right)\\ =8x^3-9-8x^3-9=-18\)

\(b.\left(x+1\right)\left(x^2-x+1\right)-\left(x-1\right)\left(x^2+x+1\right)\\ =x^3+1-\left(x^3-1\right)\\ =x^3+1-x^3+1=2\)

\(c.\left(3x-1\right)\left(3x+1\right)-\left(3x-2\right)^2\\ =9x^2-1-\left(9x^2-12x+4\right)\\ =9x^2-1-9x^2+12x-4\\ =12x-5\)

\(d.\left(2x-3\right)^2-\left(2x+3\right)\left(2x-3\right)\\ =\left(2x-3\right)\cdot\left[\left(2x-3\right)-\left(2x+3\right)\right]\\ =\left(2x-3\right)\cdot\left(2x-3-2x-3\right)\\ =\left(2x-3\right)\cdot\left(-6\right)\\ =-12x\cdot18\)

\(e.\left(3x-4\right)^2-\left(2x+4\right)^2\\ =9x^2-24x+16-\left(4x^2+16x+16\right)\\ =9x^2-24x+16-4x^2-16x-16\\ =5x^2-40x\)

\(f.\left(3x-5\right)^3-\left(3x+5\right)^3\\ =27x^3-135x^2+225x-125-\left(27x^3+135x^2+225x+125\right)\\ =27x^3-135x^2+225x-125-27x^3-135x^2-225x-125\\ =-270x^2-250\)

\(g.\left(2x-1\right)^2-\left(3x-1\right)^2\\ =4x^2-4x+1-\left(9x^2-6x+1\right)\\ =4x^2-4x+1-9x^2+6x-1\\ =-5x^2+2x\)

\(h.\left(x-2y\right)\left(x^2+2xy+4y^2\right)+\left(x^3-6y^3\right)\\ =x^3-8y^3+x^3-6y^3\\ =2x^3-14y^3\)

Bài 1:

a: \(A=3\left(x^2-2x+1\right)-\left(x^2+2x+1\right)+2\left(x^2-9\right)-\left(4x^2+12x+9\right)-5+20x\)

\(=3x^2-6x+3-x^2-2x-1+2x^2-18-\left(4x^2+12x+9\right)-5+20x\)

\(=4x^2-8x-16-5+20x-4x^2-12x-9\)

\(=-30\)

b: \(B=5x\left(x^2-49\right)-x\left(4x^2-4x+1\right)-\left(x^3+4x^2-246x\right)-175\)

\(=5x^3-245x-4x^3+4x^2-x-x^3-4x^2+246x-175\)

\(=-175\)

d: \(D=25x^2-20x+4-36x^2-12x-1+11\left(x^2-4\right)-48+32x\)

\(=-11x^2-32x+3-48+32x+11x^2-44\)

=-89